Analysis of Factors Affecting Lubrication Performance of Crankshaft Main Bearing Considering Thermal Effect - Shao Kang; Wang Guangdong; Bi Fengrong (Jixie chuandong)
In view of the factors affecting the lubrication performance of crankshaft main bearing, an elastohydrodynamic lubrication model of crankshaft main bearing, considering thermal effect, is established. The model takes the external load of bearing, bearing clearance and oil inlet temperature as variables to analyze the maximum oil film pressure, minimum oil film thickness, maximum bearing temperature and maximum friction power loss under different variables. The calculation results show that the thermal effect has a great influence on the crankshaft main bearing. When the external load of the bearing increases, the maximum oil film pressure, minimum oil film thickness and maximum friction power loss will increase; when the bearing clearance becomes smaller, the maximum oil film pressure decreases and the bearing temperature increases; when the oil inlet temperature increases, the maximum oil film pressure increases, the minimum oil film thickness decreases and the maximum friction power loss decreases.